SURGICAL COMPLICATIONS: A FORENSIC ANALYSIS OF TWO FATAL CASES - Patekar, Manoj B; Rayate, Ajinkya V; Kamble, Sangharatna M; Shinde, Amol B; Zine, Kailash U; Shinde, Rutuja.S (Journal of Forensic Medicine and Toxicology, 2025)
Surgical negligence is a term often used to describe situations in which a doctor or other healthcare professional fails to meet the standard of care required during surgery, thus resulting in injury. It is an umbrella term that covers many different types of errors such as misdiagnosis, wrong procedure, lack of postoperative monitoring. Surgical malpractice can be devastating for patients who may suffer physical harm but also emotional trauma or even death. In this paper we present two post mortem reports from cases where there was an accusation against medical practitioners for being negligent after carrying out operations on their clients. Our main objective with this case report analysis is to emphasize the need for proper surgical skills execution and care to avoid making mistakes that would lead to allegations of negligence.
Keywords: Negligence; Surgical errors; Skill; Autopsy